Equation of state of hot dense hyperonic matter in the Quark–Meson-Coupling (QMC-A) model. Issue 3 (4th January 2021) - Stone, J R; Dexheimer, V; Guichon, P A M; Thomas, A W; Typel, S
ABSTRACT: We report a new equation of state (EoS) of cold and hot hyperonic matter constructed in the framework of the quark–meson-coupling (QMC-A) model. The QMC-A EoS yields results compatible with available nuclear physics constraints and astrophysical observations. It covers the range of temperatures from T = 0 to 100 MeV, entropies per particle S/A between 0 and 6, lepton fractions from Y L = 0.0 to 0.6, and baryon number densities n B = 0.05–1.2 fm −3 . Applications of the QMC-A EoS are made to cold neutron stars (NSs) and to hot proto-neutron stars (PNSs) in two scenarios: (i) lepton-rich matter with trapped neutrinos (PNS-I) and (ii) deleptonized chemically equilibrated matter (PNS-II). We find that the QMC-A model predicts hyperons in amounts growing with increasing temperature and density, thus suggesting not only their presence in PNS but also, most likely, in NS merger remnants. The nucleon–hyperon phase transition is studied through the adiabatic index and the speed of sound c s . We observe that the lowering of ( c s / c ) 2 to and below the conformal limit of 1/3 is strongly correlated with the onset of hyperons. Rigid rotation of cold and hot stars, their moments of inertia and Kepler frequencies are also explored. The QMC-A model results are compared with two relativistic models, the chiral mean field model (CMF), and the generalized relativistic density functional (GRDF) with DD2 (nucleon-only) and DD2Y-T (full baryon octet) interactions. Similarities and differences are discussed.